FATHER INVOLVEMENT AND ACADEMIC MOTIVATION AMONG UNIVERSITY STUDENTS: THE LIMITED MEDIATING ROLE OF SELF-EFFICACY: The Limited Mediating Role of Self-Efficacy - Hikmalyansyah Hidayat; M. Zainuddin (SOSIOEDUKASI, 2026)
This study examined the relationship between father involvement, self-efficacy, and academic motivation among university students, particularly among students experiencing fatherlessness. An explanatory sequential mixed-methods design was employed involving 91 students from the Social Studies Education Program at UIN Maulana Malik Ibrahim Malang. Quantitative data were analyzed using Pearson correlation and PROCESS Macro Model 4 mediation analysis, while qualitative data were obtained through in-depth interviews and open-ended questionnaire responses. The findings showed that father involvement had a significant positive effect on academic motivation, while self-efficacy also positively predicted academic motivation. However, self-efficacy did not significantly mediate the relationship between father involvement and academic motivation. Qualitative findings revealed that fatherless students tended to experience emotional vulnerability, loneliness, and insecurity, but many developed resilience, forced independence, and survival-oriented motivation. In contrast, students with higher father involvement demonstrated greater emotional security, confidence, and academic persistence due to paternal emotional support and role modeling. Open-ended responses further indicated that emotional presence, communication, encouragement, and paternal example were perceived as more meaningful than financial support alone. Overall, the study suggests that father involvement serves as an important psychological and motivational resource in students’ academic lives, while academic motivation among fatherless students may emerge from resilience, family responsibility, and self-proof rather than self-efficacy alone.